Собственные имена в русском рекламном тексте - Бажан, Оксана Николаевна (My University, 2015)
В статье рассмотрены особенности функционирования собственных имен в русском рекламном тексте. Исследован корпус собственных имен и определено их место в русском рекламном тексте. Как показывает анализ исследуемого материала, имена собственные представляют собой яркие маркеры воздействия экстралингвистических факторов на функционирование языковых единиц. The article deals with features of functioning of proper names in the Russian advertising text. It defines and investigates the case of proper names and their place in the structure of Russian advertising text. The article decides the functions of proper names in advertising texts; analyzes the peculiarities of structures and usage of proper names in Russian advertising texts of the beginning of the 20th and the beginning of the 21st centuries.
Keywords: реклама; advertising; кафедра гуманітарних дисциплін